2006
DOI: 10.3892/or.16.1.65
|View full text |Cite
|
Sign up to set email alerts
|

The TP53 codon 72 polymorphism and predisposition to adrenocortical cancer in Polish patients

Abstract: Abstract. The TP53 polymorphism occurs at codon 72 of exon 4 with two alleles encoding either arginine or proline. The association between this common polymorphism and risk of different cancers has been extensive studied, however various reports are controversial. We have analyzed the 72Pro polymorphic variant in patients with adrenocortical tumors to evaluate whether 72G➝C substitution at codon 72 of TP53 gene may be associated with increased risk for malignancy in adrenal cortex in comparison to the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The only previously described polymorphism in ACC patients is located in exon 4, codon 72 (R72P) (19). The more frequent genotype (G/G) was found in our collective in 51 patients (70.8%) and the less frequent genotypes (G/C nZ17, C/C nZ4) in 21 patients (29.2%).…”
Section: Distribution Of Four Tp53 Polymorphisms In Acc Patientsmentioning
confidence: 72%
See 3 more Smart Citations
“…The only previously described polymorphism in ACC patients is located in exon 4, codon 72 (R72P) (19). The more frequent genotype (G/G) was found in our collective in 51 patients (70.8%) and the less frequent genotypes (G/C nZ17, C/C nZ4) in 21 patients (29.2%).…”
Section: Distribution Of Four Tp53 Polymorphisms In Acc Patientsmentioning
confidence: 72%
“…For example, while Murata et al (18) reported lung cancer to be associated with the arginine variant of the R72P polymorphism, others observed a higher prevalence of the proline variant compared with controls in such patients (17). Similarly, in the only previous study on TP53 polymorphims in ACC patients, a threefold higher prevalence of the proline variant of the R72P polymorphism compared with controls was observed (19), although in our study no such difference of TP53 R72P alleles was observed using both a larger patient sample and a larger control group. However, although our patient sample is large for a rare cancer like ACC, it is still small in comparison with studies in other malignancies (7,16,37,38).…”
Section: European Journal Of Endocrinologymentioning
confidence: 86%
See 2 more Smart Citations
“…Germline mutations of the tumour supressor p53 and overexpression of insulin-like growth factor 1 are well known to promote the development of ACC (Edgren et al, 1997;Ignaszak-Szczepaniak et al, 2006;Slater et al, 2006).…”
mentioning
confidence: 99%